Research data management as a “wicked problem” - Awre, C.; Baxter, J.; Clifford, B.; Colclough, J.; Cox, A.; Dods, N.; Drummond, P.; Fox, Y.; Gill, M.; Gregory, K.; Gurney, A.; Harland, J.; et al. (Emerald, 2015)
Purpose – The purpose of this paper is to explore the usefulness of the concept to thinking about Research Data Management (RDM). The concept of “wicked problems” seeks to differentiate very complex, intractable challenges from tamer issues where approaches to problem solving are well-understood.